Evaluation of Open Spaces in Relocated Communities Using Affordance Theory: Al-Asmarat Community as a Case Study. Issue 1 (1st August 2022) - Soliman, S; Attia, S; Khalil, H
Abstract: In 2016, the urban development facility (UDF), which was previously named as informal settlement development fund (ISDF), conducted several development projects as part of the goals of Egypt 2030's vision that supports the sustainable development goals (SDGs). UDF applies several development strategies to provide residents with better quality of life (QOL), such as relocation projects as residents move from unsafe areas to a new community where they are provided with adequate housing and basic infrastructure services. However, one major issue is that open spaces of relocated projects, despite being an important component in improving livelihoods, don't fulfill the residents' needs. Affordance theory provides the link between human behaviour and the function of space. Therefore, this paper aims to evaluate open spaces in relocated communities relying on the affordance theory. Accordingly, Al-Asmarat district, one of the relocated projects in Cairo, is investigated as a case study to evaluate open spaces and livelihood in the area. This qualitative study employed 10 in-depth interviews to obtain primary data from samples taken from relocated residents. The study ends with needed indicators to ensure that open spaces in relocated communities can afford socioeconomic activities for the residents to achieve more inclusive urban development.